Perceptions of the barriers to and the facilitators of occupational epidemiology research in the UK: a mixed methods approach. (19th October 2011) - Sweity, Samaher; Sutton, Chris; Dedman, Daniel; Downe, Soo; McElvenny, Damien
Abstract : Objectives: a) To review reported barriers to, and facilitators of, occupational epidemiological research in the UK; b) To explore perceptions of these and related issues among key UK-based researchers. Methods: A systematic literature search (1990–2010) was performed to identify studies that reported barriers and/or facilitators. Bibliographies and grey literature were also searched, and key journals were hand-searched for relevant original studies carried out in the UK and published in 2010. A narrative synthesis was undertaken. In-depth interviews of a purposive sample of 10–12 key UK-based researchers will be carried out to explore their perceptions of these issues, and the strategies they have employed to address them. Results: The systematic search revealed no empirical studies that specifically examined barriers and/or facilitators in occupational epidemiology research. These issues were mentioned in a small number of reports and expert opinion articles. Detailed results will be presented, along with results from the qualitative study. Conclusions: The systematic review reveals a gap in the literature related to occupational epidemiology research barriers and facilitators in the UK. Results from the review and the qualitative study will inform the design of the subsequent phases of the project. These include a questionnaire survey of UK researchers and stakeholders, and a multiple observational case study of 4 researchers/teams at different stages of their projects.